Effectiveness and comfort assessment of the novel intra-oral bisecting angle bisector© and paralleling rinn® digital imaging receptor holders in low palatal height patients / Afaf Syahira Ahmad Satmi … [et al.] - Ahmad Satmi, Afaf Syahira; Fadilah, Nurkamilya Halimah; Mohd Yusof, Mohd Yusmiaidil Putera; Adull Manan, Nor Fazli; Mahmud, Jamaluddin; Abdullah, Shahrul Azam (2019)
This study was performed to assess the effectiveness and comfort of two intraoral imaging techniques using respective digital radiograph receptor devices/holder in obtaining digital intraoral images. Methods: A total of 60 patients undergoing anterior intraoral periapical radiographs were single-blindly recruited. The imaging procedure was performed by two calibrated researchers where the novel holder group (Bisector©) was prospectively compared to the paralleling technique group, RINN® by performing thirty radiographic examinations, respectively. All patients were randomly segregated into different groups using block randomization method. The effectiveness of both holders was quantified based on the repeat rate percentage and quality of the images. The comfort study was enumerated using the Horizontal Visual Analogue Scale 100mm (HVAS). The Wilcoxon test (alpha = 0.05) was applied to compare the comfort score of different types of imaging receptor device reported by the patients. Results: The repeat rate percentage for Bisector© and RINN® holder devices were 8.9% and 18.6%, respectively (p<0.05). The median range of the "comfort data" according to conventional and novel intraoral radiographic receptor holder was 16 mm to 57 mm and 15 mm to 58 mm, respectively. No patients scored more than 74 mm. Conclusion: The Bisector© holder exhibited lower percentage of repeat as compared to the RINN® holder. Both groups did not cause major discomfort (mild-moderate pain). The use of novel intraoral bisecting angle radiographic receptor holder is however recommended to optimize the repeat rate in low palatal height patients.